Crystal Structure and Microstructural Growth of Gd(III)benzenetricarboxylic Metal Organic Framework (MOF) Under Facile Sonochemical Synthesis - Aini, Nur; Navidatul Rochmatul Mi’roj (The Journal of Pure and Applied Chemistry Research, 2026)
Gadolinium is one of the rare earth elements which has high magnetic susceptibility due to its 7 unpaired 4f electrons (8 µB). This magnetic susceptibility can induce both T1 and T2 relaxation in tissue where Gd substance accumulated, therefore can affect the signal of Magnetic Resonance Imaging. Gadolinium-Based Contrast Agent (GBCA) is structurally based on a complex compound formed between Gd(III) ion and certain organic ligand such as carboxylic ligand. 1,3,5-benzenetricarboxylic acid (H3BTC) ligand is one of the multicarboxylate ligands that has the potential to form GBCA through complex-based Metal Organic Framework (MOF). Gd-BTC complexes has been successfully synthesized using facile synthesis method of ultrasound wave irradiation at considerably facile time synthesis at 15, 30, and 45 minutes. The yield of white compound increases with an increase of synthesis time. The XRD powder analysis shows that the Gd-BTC complex is crystallized in a tetragonal crystal system with space group P4122. The degree of crystallinity of the obtained Gd-BTC complexes decreased as the synthesis time increased, while the crystal size increased proportionally to the synthesis time. SEM characterization displays the microrod-like morphology with various particle sizes correspond to the time ofsynthesis. Both the length and the width of the particles obtained from each complex tend to decrease along with the prolongation of synthesis time.